No evidence of transfusion transmitted sporadic Creutzfeldt‐Jakob disease: results from a bi‐national cohort study. Issue 4 (18th March 2020) - Holmqvist, Jacob; Wikman, Agneta; Pedersen, Ole Birger Vesterager; Nielsen, Kaspar René; Rostgaard, Klaus; Hjalgrim, Henrik; Edgren, Gustaf
Abstract : BACKGROUND: Creutzfeldt‐Jakob disease (CJD) is an uncommon, invariably fatal, neurodegenerative disorder that presents as progressive dementia with concurrent motor symptoms and myoclonia. The pathophysiology involves prion protein misfolding and spreading in a self‐catalyzed manner. It has been shown to be transmissible through tissue transplants. Variant CJD (vCJD), a subtype of the disease is also transmissible through transfusion of blood products. This study aims to corroborate the scarce data that suggest that sporadic CJD (sCJD) is not transmitted via blood transfusion. METHODS AND STUDY DESIGN: A retrospective cohort study was performed, using data from the bi‐national Scandinavian Donations and Transfusions (SCANDAT2) database containing data on blood donors, donations, transfusions, and transfused patients in Sweden and Denmark since 1968 and 1982, respectively. Mortality and medical data were collected from nationwide health care and population registries. Donors with subsequent CJD were identified, as well as recipients of blood products from these donors. A second analysis was performed, screening for clustering of CJD cases from donors without a CJD diagnosis. RESULTS: We identified 39 donors with a subsequent diagnosis of sCJD. No cases of CJD occurred among the 883 recipients of blood products from these donors. A total of 89 CJD cases were identified among recipients of transfusions. No clustering of cases from the same donor occurred. DISCUSSION: Using data from a large, bi‐national database of transfused patients, we find no evidence of sCJD transmission. Our data adds to the growing body of evidence indicating that sCJD is not transfusion transmitted. Abstract : See editorial on page 655–658,  in this issue